Adaptation and validation of the Adolescent Psychotic-like Symptom Screener (APSS-6) in Spain: evidence from adult population - Becerra-García, Juan Antonio; Barbeito, Sara; Petkari, Eleni; Calvo, Ana; Sánchez-Gutiérrez, Teresa (BMC Psychology, 2026)
Background: Psychotic-like experiences are common in the general population and an important indicator of psychological vulnerability. One of the used instruments for their assessment is the Adolescent Psychotic-Like Symptom Screener (APSS). However, there are few studies on the APSS psychometric characteristics in different cultural contexts. The aim of this study is to adapt the instrument in the Spanish context and analyze its psychometric properties in an adult population. Methods: Upon the translation and adaptation of the APSS to Spanish, a sample of 287 participants (19-60 years) completed the questionnaire online together with the Symptom Assessment-45 Questionnaire (SA-45) and an ad-hoc survey on clinical and sociodemographic variables. The sample was then randomly split into two halves, the first being the calibration (n = 144) and the second the validation sample (n = 143). An exploratory factor analysis was performed with the former, and a confirmatory factor analysis was performed with the latter, together with internal consistency and convergent validity analyses. Results: The APSS Spanish version presents a unifactorial structure comprising 6 out of the 7 original items with adequate fit and good internal consistency. This single factor structure is invariant across age, sex and history of self-reported psychopathology. The instrument also shows significant positive correlations with the SA-45 psychoticism and paranoid ideation subscales. Conclusions: To the best of our knowledge, this is the first study that has conducted a psychometric analysis of the APSS in adult population. The Spanish version of the APSS shows adequate reliability, construct and convergent validity in adults, therefore provides a handy tool to be used for the screening of psychotic-like experiences in the Spanish general population.
Keywords: APSS; psychotic-like experiences; factorial structure; psychometric properties; psychoticism; paranoid ideation